Global atmospheric eﬀects on the gravity ﬁeld quantities - TENZER, Robert; VAJDA, Peter; HAMAYUN, K (Contributions to Geophysics and Geodesy, 2009)
We compile  the global  maps  of atmospheric eﬀects  on the gravity ﬁeld quantities  using the spherical harmonic representation of the gravitational ﬁeld.   A simple atmospheric density distribution is assumed within  a lower  atmosphere (< 6 km).   Dis- regarding temporal and  lateral  atmospheric density variations,  the  radial atmospheric density model is deﬁned as a function  of the nominal  atmospheric density at the sea level and the height.  For elevations above  6 km, the atmospheric density distribution from the United  States Standard Atmosphere 1976 is adopted. The 5 × 5 arc-min  global  elevation data  from the ETOPO5 are used to generate the global elevation model coeﬃcients. These coeﬃcients (which  represent the geometry of the lower bound  of atmospheric masses) are utilized  to compute the atmospheric eﬀects  with a spectral resolution complete to degree and  order  180.  The atmospheric eﬀects  on gravity disturbances, gravity anomalies and geoid undulations are evaluated globally on a 1 × 1 arc-deg  grid.